Is seasonal vaccination a contributing factor to the selection of influenza epidemic variants? - Yong Chong; Hideyuki Ikematsu (Taylor & Francis Group, 2018)
Influenza A/H3N2 viruses are the most common and virulent subtypes for humans. Antigenic drift, changes in antigenicity through the accumulation of mutations in the hemagglutinin (HA) gene is chiefly responsible for the continuing circulation of A/H3N2 viruses, resulting in frequent updates of vaccine strains based on new variant analyses. In humans, these drift-related mutations are considered to be primarily caused by the immune pressure elicited by natural infection. Whether or not the immune pressure elicited by vaccination (vaccine pressure) can have a certain effect on drift-related mutations is unclear. Recently, our findings suggested the possible effect of vaccine pressure on HA mutations by directly comparing amino acid differences from the corresponding vaccine strains between isolates from vaccinated and unvaccinated patients. It is possible that influenza vaccine pressure selects variants genetically distant from the vaccine strains. Considering the effect of vaccine pressure on HA mutations would contribute to further understanding the mechanism of antigenic drift, which would be helpful for predicting future epidemic viruses.